Summer and winter variations of dicarboxylic acids, fatty acids and benzoic acid in PM2.5 in Pearl Delta River Region, China - K. F. Ho; S. S. H. Ho; S. C. Lee; K. Kawamura; S. C. Zou; J. J. Cao; H. M. Xu (Atmospheric Chemistry and Physics, 2011)
Ground-based PM2.5 samples collected at four different sites in Pearl River Delta region (PRD) during winter and summer (from 14 December 2006 to 28 January 2007 in winter and from 4 July to 9 August 2007 in summer) were analyzed for 30 water-soluble organic species, including dicarboxylic acids, ketocarboxylic acids and dicarbonyls, nine fatty acids, and benzoic acid. Molecular distributions of dicarboxylic acids demonstrated that oxalic acid (C2) was the most abundant species followed by phthalic acid (Ph) in PRD region. The concentrations of total dicarboxylic acids ranged from 99 to 1340 ng m−3, with an average of 438 ± 267 ng m−3 in PRD. The concentrations of total ketocarboxylic acids ranged from 0.6 to 207 ng m−3 (43 ± 48 ng m−3 on average) while the concentrations of total α-dicarbonyls, including glyoxal and methylglyoxal, ranged from 0.2 to 89 ng m−3, with an average of 11 ± 18 ng m−3 in PRD. The total quantified water-soluble compounds (TQWOC) (organic carbon) accounted for 3.4 ± 2.2% of OC and 14.3 ± 10.3% of water-soluble OC (WSOC). Hexadecanoic acid (C16:0), octadecanoic acid (C18:0) and oleic acid (C18:1) were the three most abundant fatty acids in PRD. The distributions of fatty acids were characterized by a strong even carbon number predominance with a maximum (Cmax) at hexadecanoic acid (C16:0). Ratio of C18:1 to C18:0 acts as an indicator for aerosol aging. In PRD, an average of C18:1/C18:0 ratio was 0.53 ± 0.39, suggesting an enhanced photochemical degradation of unsaturated fatty acid. Moreover, the concentrations of benzoic acid ranged from 84 to 306 ng m−3, (165 ± 48 ng m−3 on average), which can be emitted as primary pollutant from motor vehicles exhaust, or formed from photochemical degradation of aromatic hydrocarbons. Seasonal variations of the organic specie concentrations were found in the four sampling cities. Higher concentrations of TQWOC were observed in winter (598 ± 321 ng m−3) than in summer (372 ± 215 ng m−3). However, the abundances of TQWOC in OC mass were higher in summer (0.9–12.4%, 4.5 ± 2.7% on average) than in winter (1.1–5.7, 2.5 ± 1.2% on average), being consistent with enhanced secondary production of dicarboxylic acids in warmer weather. Spatial variations of water-soluble dicarboxylic acids were characterized by higher concentrations in Hong Kong and lower concentrations in Guangzhou (GZ)/Zhaoqing (ZQ) during winter whereas the highest concentrations were observed in GZ/ZQ during summer. These spatial and seasonal distributions are consistent with photochemical production and the subsequent accumulation under different meteorological conditions.